New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae). Part II - Ranasinghe, Sasanka; Eberle, Jonas; Athukorala, Namal; Benjamin, Suresh P.; Ahrens, Dirk (European Journal of Taxonomy, 2022)
Here, we present the results of our field survey in Sri Lanka and describe ten new species of Sericini: Selaserica fabriziae sp. nov., Sel. sororinitida sp. nov., Neoserica pophami sp. nov., Maladera haniel sp. nov., M. kishi sp. nov., M. windy sp. nov., M. karunaratnae sp. nov., M. hiyarensis sp. nov., M. dambullana sp. nov., and M. deenstana sp. nov. All seven of the newly described species of Maladera belong to the M. fistulosa species group, which is an endemic radiation on the island that is characterized by entirely reduced or fused parameres. An updated key to the Maladera fistulosa group is provided. Further, new locality records for 23 already known species are given. The genitalia and habitus of all new species are illustrated, the distribution of the new species is shown with maps.